The association of plasminogen activator inhibitor-1 level with ischemic stroke (preliminary study) (Medical Journal of Indonesia, 2010)
Aim Recently, increased plasminogen activator inhibitor-1 (PAI-1) has been known a risk factor for ischemic heart disease. However, the association of increased PAI-1 level with ischemic stroke remains unclear. The aim of this study was to analyze the association of PAI-1 level with ischemic stroke. Methods By case control design we involved 38 ischemic stroke and 38 risky-matched control subjects who fulfilled the criteria. The PAI-1 level was determined by ELISA method using Asserachrom PAI-1 from Stago. Results High PAI-1 level was found more frequent in ischemic stroke subjects than in control subjects (21.1% vs. 7.9 % with OR 3.1; 95 % CI 0.757 - 12.790). The analysis of all studied subjects showed that there was a weak negative correlation between PAI-1 level and age (r = -0.4; P = 0.000). High PAI-1 level was found more frequent in younger (40 - 58 years old) than in the older subjects (60 - 84 years old) (20% vs. 9.8 %) (p=0.004). Conclusion The result of this preliminary study suggested an association between PAI-1 level and ischemic stroke in younger age. Further study with larger subjects is recommended to confirm this association. (Med J Indones 2009;19:158-63)